Genotype-environment interaction for cob yield and maturity in baby corn (Zea mays L.) (Bangladesh Journal of Agricultural Research, 2010)
Genotype-location interaction and phenotypic stability of cob yield and maturity parameters of eight baby corn genotypes including hybrids and composite varieties were assessed during rabi 2006-2007. Significant genotype-environment interactions were observed for all the characters under study. Pooled deviations were also found significant for all the characters except days to harvesting. The genotype Khoibhutta was found stable for days to tasselling, days to harvesting and yield of by product and suited to unfavourable environment. On the other hand, the BBC1 was stable across environments for days to harvesting and cob yield. Genotype NS pop corn was stable for days to tasselling and suited to unfavourable environment and stable for yield of by-product and cob yield across the environments. The genotype BHM5 showed stable performance only for cob yield across the environments. Keywords: Stability; genotype; environment; G × E; yield components; baby corn. DOI: 10.3329/bjar.v35i3.6455Bangladesh J. Agril. Res. 35(3) : 489-496